Associations of urinary 8‐iso‐prostaglandin F2α levels with all‐cause dementia, Alzheimer's disease, and vascular dementia incidence: results from a prospective cohort study. Issue 5 (12th April 2020) - Trares, Kira; Gào, Xīn; Perna, Laura; Rujescu, Dan; Stocker, Hannah; Möllers, Tobias; Beyreuther, Konrad; Brenner, Hermann; Schöttker, Ben
Abstract: Introduction: Prospective studies on a potential association of 8‐iso‐prostaglandin F2α (8‐iso‐PGF2α ) levels, a biomarker of lipid peroxidation, with dementia are limited. Methods: Multivariate Cox regression models were used to assess potential associations of urinary 8‐iso‐PGF2α levels with all‐cause, Alzheimer's disease (AD), and vascular dementia (VD) incidence in 5853 older adults from a German, population‐based cohort. Results: Over 14 years of follow‐up, 365 all‐cause dementia cases including 127 VD and 109 AD cases were diagnosed. Participants in the top compared to the bottom 8‐iso‐PGF2α tertile had a 45% increased risk of all‐cause dementia incidence (hazard ratio [95% confidence interval]: 1.45 [1.12 to 1.88]). Interaction with the apolipoprotein E (APOE) ԑ4/ԑ4 genotype was detected ( P = .02). Furthermore, continuously modeled, logarithmized 8‐iso‐PGF2α levels were statistically significantly associated with all‐cause dementia and AD incidence. Discussion: Oxidative stress may be involved in the pathogenesis of dementia. Individuals with increased 8‐iso‐PGF2α levels and the APOE ԑ4/ԑ4 genotype showed a considerably increased dementia risk.